Are cell phones an indicator of personal exposure to organophosphate flame retardants and plasticizers?. (January 2019) - Yang, Congqiao; Harris, Shelley A.; Jantunen, Liisa M.; Siddique, Shabana; Kubwabo, Cariton; Tsirlin, Dina; Latifovic, Lidija; Fraser, Bruce; St-Jean, Melissa; De La Campa, Regina; You, Hongyu; Kulka, Ryan; et al.
Abstract: Background: Exposure to organophosphate ester (OPE) flame retardants and plasticizers is widespread and is of concern due to their toxicity. Objectives: To investigate relationships between and within OPE concentrations in air, dust, hands, electronic product wipes and urinary metabolites with the goal of identifying product sources and exposure pathways. Methods: Women in Toronto and Ottawa, Canada, provided a urine sample, two sets of hand wipes, access to their homes for air and dust sampling, and completed a questionnaire. OPE concentrations were obtained for air and floor dust in the bedroom (n = 51) and most used room (n = 26), hand wipes (n = 204), and surface wipes of handheld (n = 74) and non-handheld electronic devices (n = 125). All air, dust and wipe samples were analyzed for 23 OPE compounds; urine samples (n = 44) were analyzed for 8 OPE metabolites. Results: Five-8 OPEs were detected in >80% of samples depending on the sample type. OPE median concentrations in hand wipes taken 3 weeks apart were not significantly different. Palms had higher concentrations than the back of hands; both were significantly correlated. Concentrations of 9 OPEs were significantly higher in surface wipes of handheld than non-handheld electronic devices. Six OPEs in hand wipes were significantly correlated with cell phone wipes, with two to four OPEs significantly correlated with tablet, laptop and television wipes. Multiple regression models using hand wipes, cell phone wipes and dust explained 8–33% of the variation in creatinine-adjusted urinary metabolites; air concentrations did not have explanatory power. OPEs in cell phone wipes explained the greatest variation in urinary metabolites. Conclusions: Handheld electronic devices, notably cell phones, may either be sources or indicators of OPE exposure through hand-to-mouth and/or dermal uptake. Graphical abstract: Unlabelled Image Highlights: OPE urinary metabolites in women 18–44 related to parent compounds on cell phones. OPE levels on hands correlated with those on cell phones and other handheld devices. OPE concentrations higher on surfaces of handheld than non-handheld electronics OPE urinary metabolites not related to levels in residential air Cell phones may be a source and indicator of OPE exposure.